Willemite-Based Glass Ceramic Doped by Different Percentage of Erbium Oxide and Sintered in Temperature of 500-1100C Physical and Optical Properties - Sarrigani, Gholamreza Vahedi; Amiri, Iraj Sadegh (SpringerBriefs in Electrical and Computer Engineering,, 2019)
This book investigates the effect of sintering temperature on willemite based glass-ceramic doped with different content of Er2O3. It is the first to report research on producing willemite by using waste materials and using trivalent erbium (Er3+) as a dopant. This book provides a survey of the literature on glass and glass-ceramic, while comprehensive experiments and analysis have been performed on the material used. .